Rare bird documentation form for Lesser Black-backed Gull at Red Rock Reservoir, 1997 - Dinsmore, Stephen J.et al (1997)
Rare bird documentation form for a Lesser Black-backed Gull at Red Rock Reservoir in Marion County, IA on December 26, 1997 and December 30, 1997. Epson - sheet feed